ABU RAYHAN BERUNI – AN ENCYCLOPEDIA SCIENTIST WHO WROTE WORKS IN VARIOUS FIELDS OF SCIENCE - Avliyokhonov Saidakbarkhon (The Conference Hub, 2025)
The article analyzes information about the life, scientific activities and famous works of the encyclopedist Abu Rayhan Beruni. It also presents the research of modern researchers on the scientific heritage of Beruni and the activities carried out in New Uzbekistan related to the name of Beruni.
Keywords: Beruni, science, Samani, Ghaznavi, natural and social sciences.